Early Post-trauma Interventions in Organizations: A Scoping Review - Richins, Matt T.; Gauntlett, Louis; Tehrani, Noreen; Hesketh, Ian; Weston, Dale; Carter, Holly; Amlôt, Richard (Frontiers in Psychology, 2020)
Background. In some organisations, traumatic events via direct or indirect exposure are routine experiences. A NICE review (2005; updated in December 2018) of Post-Traumatic Stress Disorder (PTSD) management in primary and secondary care did not address early interventions for trauma in emergency response organisations. Aims. This scoping review was designed to identify previous research which evaluated the use of early interventions following exposure to primary or secondary trauma, to report on the effectiveness of early interventions models. Method. A scoping review was conducted to examine early interventions for trauma with staff in roles potentially exposed to trauma including: emergency response, military and humanitarian aid. Relevant data was extracted from included studies and outcomes were assessed using meta-ethnography. Results. Fifty studies of mixed quality met the inclusion criteria for this review. Synthesis of study outcomes found that early interventions help emergency responders to manage post-incident trauma when they: are delivered in a manner that respects distinct organisational culture; are supported by organisations and senior management, and; harness existing social cohesion and peer support systems within teams. Conclusions. This review demonstrates that early interventions support emergency responders following exposure to trauma when: tailored to the needs of the population, are supported by the host organisation, and harness existing social cohesion and peer support processes within a team or unit. We identify a number of recommendations for the delivery and evaluation of early interventions for psychological trauma in emergency response organisations.